Subject matters of Organizational Communication and of Public Relations: a contextual outlook - Oliveira, Ivone de Lourdes (Organicom, 2009)
This text aims to instigate discussions about the field of Communication within the context of organizations and at the same time to establish some parameters that help us to understand the thin line between this field and Public Relations accreditation. To better clarify the theme, and recognizing its complexity, our approach includes reflections on both subject matters – communication in the context of organizations and Public Relations. Epistemological questions and the complexity of the organizational world are also added to the reflection.